2020
DOI: 10.1111/lapo.12158
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of regulatory discretion

Abstract: Regulatory authorities in the utilities sector typically employ economic evidence and analysis to make expert discretionary judgments under uncertainty. However, economic analysis does not provide clear answers regarding policy outcomes. This exposes regulators to environmental uncertainty, that is, uncertainty regarding the reactions of other actors in the institutional system to their decisions. When policy outcome and environmental uncertainty are high, discretion takes center stage. Will regulators pursue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Whenever laws delegate authority or power to regulations, they can shape the discretion granted to make regulations. Existing studies on regulatory discretion consider regulation within the context of the discretion of regulatory agencies (Mantzari & Vantaggiato, 2020; Schmidt & Scott, 2021). However, they do not provide a clear nominal definition of the term that can be measured over time.…”
Section: Regulatory Discretion: Conceptualizationmentioning
confidence: 99%
“…Whenever laws delegate authority or power to regulations, they can shape the discretion granted to make regulations. Existing studies on regulatory discretion consider regulation within the context of the discretion of regulatory agencies (Mantzari & Vantaggiato, 2020; Schmidt & Scott, 2021). However, they do not provide a clear nominal definition of the term that can be measured over time.…”
Section: Regulatory Discretion: Conceptualizationmentioning
confidence: 99%
“…This study concluded the fiduciary logic of economic regulation and the agency logic of social regulation were conducive to conflict in actual regulatory compliance. Another study of UK utility regulators found less reliance on privileging "economic argument" to support regulatory decisions when the regulator felt "environmental uncertainty" from, for example, the threat of legal challenge or from government interference (Mantzari & Vantaggiato, 2020). Notably, the gas and electricity regulator's uncertainty heightened when its statutory mandate was expanded to consider environmental, supply, and affordability factors, and its "policy space" was shared with another agency.…”
Section: The Differing Goals Of Regulatory Regimesmentioning
confidence: 99%
“…They focus on the delegation of regulatory authority to independent regulatory agencies (Gilardi, 2008; Hansen, 2023; Maggetti, 2007, 2012; Maggetti et al, 2022; Thatcher, 2002; Thatcher & Sweet, 2002), despite the fact that they normally lack the authority to make regulations through delegated legislation. In European studies on regulatory discretion, the focus has primarily been on how regulators exercise discretion when overseeing markets (Mantzari & Vantaggiato, 2020), or the focus has been on discretion in a regulatory capitalism context (Schmidt & Scott 2021). In contrast, “Americanists” pay considerable attention to how Congress delegates and controls rulemaking powers of regulatory agencies (Yackee & Yackee, 2016).…”
Section: Dimensions and Styles Of Regulatory Discretionmentioning
confidence: 99%